The effects of wearing lower body compression garments during a cycling performance test - Driller, M. W.; Halson, S. L. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Compression garments have been commonly used in a medical setting as a method to promote blood flow. Increases in blood flow during exercise may aid in the delivery of oxygen to the exercising muscles and, subsequently, enhance performance. The aim of the current study was to investigate the effect of wearing lower body compression garments during a cycling test. Methods: Twelve highly trained cyclists (mean ± SD age 30 ± 6 y, mass 75.6 ± 5.8 kg, VO2peak 66.6 ± 3.4 mL /kg·min) performed two 30-min cycling bouts on a cycle ergometer in a randomized, crossover design. During exercise, either full-length lower body compression garments (COMP) or above-knee cycling shorts (CON) were worn. Cycling bouts involved 15 min at a fixed workload (70% of VO2max power) followed by a 15-min time trial. Heart rate (HR) and blood lactate (BL) were measured during the fixed-intensity component of the cycling bout to determine the physiological effect of the garments. Calf girth (CG), thigh girth (TG) and perceived soreness (PS) were measured preexercise and postexercise. Results: COMP produced a trivial effect on mean power output (ES = .14) compared with CON (mean ± 95% CI 1.3 ±1.0). COMP was also associated with a lower HR during the fixed-workload section of the test (-2.6% ± 2.3%, ES = -.38). There were no differences between groups for BL, CG, TG, and PS. Conclusion: Wearing compression garments during cycling may result in trivial performance improvements of ~1% and may enhance oxygen delivery to the exercising muscles.